Is there a 'marriage premium' for gay men? - Madeline Zavodny (Institute for the Study of Labor (IZA), 2007)
It is well-known that married men earn more than comparable single men, with typical estimates of the male marriage premium in the range of 10 to 20 percent. Some research also finds that cohabiting men earn more than men not living with a female partner. This study uses data from the General Social Survey and the National Health and Social Life Survey to examine whether a similar premium accrues to gay men who live with a male partner and whether cohabiting gay men have different observable characteristics than non-cohabiting gay men. Controlling for observable characteristics, cohabiting gay men do not earn significantly more than other gay men or more than unmarried heterosexual men. Cohabiting heterosexual men also do not earn more than non-cohabiting heterosexual men.
Keywords: J12; 300; Male marriage premium; gay; heterosexual; Lohn; Männliche Arbeitskräfte; Ehe; Homosexualität; USA